2020
DOI: 10.1002/ange.202010437
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrochemical Hydrolysis of Hydrosilanes to Silanols via Anodically Generated Silyl Cations

Abstract: The first electrochemical hydrolysis of hydrosilanes to silanols under mild and neutral reaction conditions is reported. The practical protocol employs commercially available and cheap NHPI as ah ydrogen-atom transfer (HAT) mediator and operates at room temperature with high selectivity,leading to various valuable silanols in moderate to good yields.N otably,t his electrochemical method exhibits ab road substrate scope and high functional-group compatibility,and it is applicable to late-stage functionalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…To understand the possible reaction mechanism, the effects of silane and water on the reaction were tested using Ph 2 SiD 2 and D 2 O. The kinetic isotope effects ( k H / k D ) based on the reaction of Ph 2 SiD 2 and H 2 O were 2.95 and 1.78 at 7 and 12 min, respectively, suggesting that the Si–H bond cleavage might be involved in the rate-determining step (eqs 1–4). , Meanwhile, the reaction of Ph 2 SiH 2 and D 2 O was also carried out, and the k H / k D value was calculated to be around 1.03, which showed that the water O–H bond cleavage was not the rate-determining step. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the possible reaction mechanism, the effects of silane and water on the reaction were tested using Ph 2 SiD 2 and D 2 O. The kinetic isotope effects ( k H / k D ) based on the reaction of Ph 2 SiD 2 and H 2 O were 2.95 and 1.78 at 7 and 12 min, respectively, suggesting that the Si–H bond cleavage might be involved in the rate-determining step (eqs 1–4). , Meanwhile, the reaction of Ph 2 SiH 2 and D 2 O was also carried out, and the k H / k D value was calculated to be around 1.03, which showed that the water O–H bond cleavage was not the rate-determining step. , …”
Section: Resultsmentioning
confidence: 99%
“…The kinetic isotope effects (k H /k D ) based on the reaction of Ph 2 SiD 2 and H 2 O were 2.95 and 1.78 at 7 and 12 min, respectively, suggesting that the Si−H bond cleavage might be involved in the rate-determining step (eqs 1−4). 66,67 Meanwhile, the reaction of Ph 2 SiH 2 and D 2 O was also carried out, and the k H / k D value was calculated to be around 1.03, which showed that the water O−H bond cleavage was not the rate-determining step. 19,68 Catalytic results, as shown in Table 1, disclosed that the metal Ir(III) center in the porphyrin ring played an important role in the efficiency.…”
Section: Experimental and Computational Sectionmentioning
confidence: 99%
“…In 2021, Zhang and co-workers reported an electrochemical protocol that allows the highly selective transformation of hydrosilanes to silanols (Scheme 26). 101 Notably, these neutral and mild conditions exhibited a broad substrate scope and high functional group compatibility. A wealth of trisubstituted silanes carrying different electronically and sterically varied functional groups reacted well in this process, delivering the desired silanols with good yields.…”
Section: Electro-generated Silyl Radicals By Anodic Oxidationmentioning
confidence: 99%
“…School of Chemistry and Materials Science, University of Science and Technology of China, Jinzhai Road 96, Hefei 230026, China. E-mail: binxiao@ustc.edu.cn C-Ge bond energy and oxidative potentials (Table 1), [18][19][20][21][22][23] allowing many types of germanium compounds to be active under the same conditions. Moreover, organogermanium compounds are usually regarded as non-toxic, 24 which would meet one of the key requirements of modern organic synthesis.…”
Section: Bin Xiaomentioning
confidence: 99%